2017
DOI: 10.3390/s18010014
|View full text |Cite
|
Sign up to set email alerts
|

Automating the Timed Up and Go Test Using a Depth Camera

Abstract: Fall prevention is a human, economic and social issue. The Timed Up and Go (TUG) test is widely used to identify individuals with a high fall risk. However, this test has been criticized because its “diagnostic” is too dependent on the conditions in which it is performed and on the healthcare professionals running it. We used the Microsoft Kinect ambient sensor to automate this test in order to reduce the subjectivity of outcome measures and to provide additional information about patient performance. Each pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Due to a variety of reasons, including socioeconomic [5], automated solutions for some of these tests have appeared. A significant motivator for the automation of these tests is the elimination of human error [3,[6][7][8].…”
Section: Patient Evaluation Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to a variety of reasons, including socioeconomic [5], automated solutions for some of these tests have appeared. A significant motivator for the automation of these tests is the elimination of human error [3,[6][7][8].…”
Section: Patient Evaluation Testsmentioning
confidence: 99%
“…With an acknowledged need for automating the TUG and FTSTS tests [5], several sensor-based systems have been proposed in the literature. These are reviewed based on the type of sensors used.…”
Section: Portable Sensing Tele-rehabilitation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the subjects are not necessarily asked to perform TUG test even they did in our experiment. We need not try to identify the phases of TUG test as others did [14][15][16] [17]. This makes the method automatic, unobtrusive and easy to deploy at any setting.…”
Section: Discussionmentioning
confidence: 99%
“…Skeleton data and depth data of Kinect were utilized for detecting six phases of TUG test. Dubois, et al identified the phases of TUG test from the depth data of Kinect camera and additionally, extracted several gait related parameters to classify the subjects as with low or high fall risk [17].…”
Section: Related Researchmentioning
confidence: 99%